The Cost of Equity in Emerging Markets: The Case of Latin America (2013)
We applied ten methods to calculate the cost of equity in a set of companies included in the MSCI1 emerging markets list from five countries in Latin America. The methods modify the discount rate obtained using the standard Capital Asset Pricing Model (CAPM) by adjusting for country risk premiums. We found that country effects are more important than industry effects in Latin America. This work also contributes to a better understanding of how different ways of calculating country risk can affect a firm¿s cost of equity. Further-more, it gives empirical evidence for specific country and industry determinants of the cost of equity that are not explicitly treated in the extant literatura.